Concurrent Iliopsoas Abscess and Septic Arthritis of the Hip in a Young Adult with Poorly Controlled Type 1 Diabetes Mellitus: A Case Report - Sepideh Aarabi (Case Reports in Clinical Practice, 2026)
A 28-year-old woman with poorly controlled type 1 diabetes mellitus (T1DM) presented with a two-week history of fever, left lower back pain, and progressive difficulty walking. Imaging confirmed the concurrent presence of a left iliopsoas abscess and left hip septic arthritis—an exceedingly rare combination. The abscess was treated with CT-guided percutaneous catheter drainage, and the hip joint infection was managed with open arthrotomy and irrigation. Culture of aspirated material identified methicillin-resistant Staphylococcus aureus (MRSA). Treatment was completed with a six-week course of targeted intravenous vancomycin and concurrent optimization of glycemic control. Complete clinical, laboratory, and radiological resolution was documented at six months. This case highlights that clinicians should maintain a high index of suspicion for concurrent deep-seated infections in diabetic patients presenting with musculoskeletal symptoms and fever. MRI is the imaging modality of choice for delineating both pathologies simultaneously, and successful management necessitates a multidisciplinary approach integrating surgical drainage, pathogendirected antimicrobial therapy, and metabolic optimization.